RTPDB: a database providing associations between genetic variation or expression and cancer prognosis with radiotherapy-based treatment. (30th October 2018) - Zhang, Cheng-Dong; Yang, Yuan; Chen, Huan-Huan; Zhang, Ting; Wang, Qiang; Liang, Yuan; Zhang, Liang; Zhou, Yan
Abstract: In recent years, lots of studies have reported the relationship between genetic variation or expression and cancer prognosis with radiotherapy-based treatment. However, due to limitation in available journals or literature database, inconsistent nomenclature system of genetic variation and cancer and time-consuming investigation on literature searching and reading, considerable researches could hardly get found and cited. In this study, we constructed the Radiotherapy Prognosis Database (RTPDB), which contains a comprehensive resource about genes and related cancer prognosis. It included 775 studies, which consist of 275 Single Nucleotide Polymorphism (SNP) studies with 59 765 patients, 261 genes, 708 SNPs, 16 tumors and 16 treatment types, and 500 expression studies with 55 751 patients, 264 genes, 27 tumors and 15 treatment types. The names of genes and their variants were converted and displayed in the form of the official symbol. The detailed information of the tumor, treatment and prognosis were classified. We hope RTPDB will be a useful resource with great potential for researches on genes, variants and cancer prognosis.